Water activity in foods: Fundamentals and applications - Gustavo V. Barbosa - Cánovas; Fontana Jr, Anthony J.; Schmidt, Shelly J.; Labuza, Theodore P. (Wiley, 2020)
This second edition of Water Activity in Foods furnishes those working within food manufacturing, quality control, and safety with a newly revised guide to water activity and its role in the preservation and processing of food items.